TERAPI BIOLOGIK PADA PASIEN PSORIASIS - Thaha, Athuf (Jurnal Kedokteran Brawijaya, 2008)
ABSTRACT Treatment  limitations  of  current  immunosuppressive  therapies,  and  growing  understanding  of  psoriasispathogenesis on a molecular level have stimulated much interest in the field of immunomodulatory therapy fomanagement of psoriasis. Genetic engineering has allowed the development of proteins that are targeted tospecific cell surface receptors. A well over 40 targeted biologic agents are in preclinical and clinical testing foT-cell  mediated  inflammatory    diseases,  including  psoriasis.  It  is  important  that,  as  a  doctor  become  weleducated in biologics, since several of these agents are available for the management of psoriasis.   Keywords:  immunosuppressive  therapy,  immunomodulatory  therapy,  genetic  engineering,  surface  receptors,  targetedbiologic agents, biologics.